Pilihan Rasional Perempuan Entrepreneur dalam Gugat Cerai di Kota Batam - Rahmawati; Sri Wahyuni; Emmy Solina (Pusat Studi Gender, Universitas Kristen Indonesia, 2023)
Divorce suit is a claim of rights to court filed by a wife to divorce from her husband. The divorce is triggered by several factors, one of which dominates is the problem of conflicting disputes continuously, while the rest of the economic factors. The independence of women in the economy is assumed to be a trigger for divorce decisions. Where this condition is a woman who has higher income than her husband and the woman feel enough to have day-to-day needs. This is the basis for the view of women's economic independence will allow women to choose divorce as a rational action in resolving the marital crisis. This study aims to determine the entrepreneur women in divorce suit where until now women who dominate can sue for divorce. The theory that the researcher uses is the theory of rational choice in which an action has an achievement or goal of the decision taken. This study uses qualitative research. Technique to determine the informant by using purposive sampling. The result of this study findings is awareness in terms of how women entrepreneurs can decide a divorce suit decision. Women also have reasons to divorce, one of which is financial ability, educational ability, the ability to educate children, and the ability to deal with social life.